Analisis Faktor-Faktor yang berhubungan dengan kinerja bidan dalam pengisian buku KIA pada deteksi dini kehamilan risiko tinggi di puskesmas Kota Bukittinggi - Liza Andriani; Mega Ade Nugrahmi (Sekolah Tinggi Ilmu Kesehatan Yatsi, 2020)
The management of KIA program aims to strengthen and increase the reach and quality of KIA services effectively and efficiently. Today's strengthening of KIA services is prioritized on main activities, one of which is increasing early detection of risk factors and complications of obstetrics and neonates by health personnel. This study aims to analyze the factors associated with the performance of midwives in filling out the KIA handbook on early detection of high risk pregnancies. The research used is analytical and the independent variable is the level of knowledge, attitude, motivation and workload, and the dependent variable is the midwife performance. The population in the study was 37 respondents and the sampling technique was carried out by total sampling, the research data collection was carried out by using a questionnaire and observation sheet. The results of the study prove that the performance of midwives in filling out the KIA book has poor performance (62.2%), high level of knowledge (51.4%), poor attitude (51.4%), good motivation (67.6%) and light workload (83.8%). The results of multivariate analysis, it was found that the factor most related to the performance of midwives in filling out the KIA handbook was the attitude variable. Based on the research, it was concluded that the midwife would have a good performance in filling out the KIA book if it was based on a high level of knowledge, a positive attitude, high motivation, and supported by complete facilities.